A simple DPSS laser setup and experiments for undergraduates. (8th December 2016) - Bergmann, Antje; Kircher, Sandra; Setzler, Dominik; Gerharz, Miriam; Rockstuhl, Carsten
Abstract: Advanced optical concepts are often thought to be out of reach when it comes to an experimental demonstration for undergraduates and secondary school students. This is not always true. Here, we discuss the use of a diode-pumped solid state (DPSS) laser based on Nd:YVO4 /KTP hybrid crystals, being also at the heart of many green laser pointers, to educate students on multiple modern optical concepts and applications thereof. This concerns not only nonlinear optics, e.g. second harmonic generation, but also laser physics and electromagnetic wave phenomena that occur if light interacts with matter. In this contribution we primarily describe the setup of the simple Nd:YVO4 /KTP solid state laser system using hybrid crystals. The setup is integrated into our lab for undergraduates and school students. We show that various experiments on the topics mentioned above can be performed with affordable equipment while investigating some basic laser characteristics. By studying the influence of different surface roughness from various materials on the appearance of laser speckles, students get to know a modern laser application. Furthermore, we describe an experiment on the optical data transfer in free space optical communication: an additional experiment with a high motivational nature.